Nature-based nanocomposites for adsorption and visible light photocatalytic degradation of methylene blue dye - Yontar, Arife Kubra; Avcioglu, Suna; Cevik, Sinem (ELSEVIER SCI LTD, 2022)
Demands for sustainable and eco-friendly materials for environmental remediation have increased the interest in bio-reinforced nanocomposites. Herein, novel plant extracts modified polyvinyl alcohol (PVA) nanocomposite films were fabricated using Hemp seeds, St. John's Wort, Rosemary, and Cherry Laurel plants, and their pho-tocatalytic activities were investigated for the photodegradation of Methylene Blue (MB) dye. Besides, bio-reinforced nanocomposites were characterized by various techniques to investigate the influence of plant ex-tracts on the chemical structure, morphology, hardness, and swelling ratio of nanocomposite films. The morphological inspections revealed that as a result of the plant-extract modification, the PVA matrix was rein-forced with equiaxed nanoparticles in a size range from 20 to 250 nm. The Shore-D hardness and the water absorption capacities of fabricated bio-reinforced nanocomposites were found to be 1.86 and 1.24 times higher than their neat counterparts, respectively. Both the bio-reinforced nanocomposites films showed considerably enhanced photocatalytic activity for MB dye degradation relative to neat PVA film. With a synergetic effect of adsorption and photocatalytic degradation, 61.3% of MB dye could be removed under light irradiation by Rosemary and Cherry Laurel modified PVA nanocomposite film. Therefore, the present bio-reinforced nano -composites with photocatalytic activity shed light on the unknown potential of plant extracts.
Keywords: Photocatalysis; Plant extracts; Green nanocomposite; Dye degradation; Methylene blue; GREEN SYNTHESIS; NANOPARTICLES; MECHANISMS; LEAF; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology